Front-page Scotland - Patrick, David (Historian), author.
1 online resource.
Keywords: This book provides a varied, thorough and informative analysis of how newspapers covered the 2014 Scottish independence referendum in its critical final months. Providing a wealth of new empirical findings, the book engages with the key themes and issues presented by a variety of newspaper outlets. These main observations include: a major focus on the economic aspects of the debate; persistent concerns regarding an independent Scotland's prospects on the world stage, both militarily and strategically; the re-emergence of Gordon Brown as a political heavyweight; and a myopic focus on Alex Salmond, who would come to be framed as personally synonymous with the abstract concept of Scottish independence. The book will be the first point of contact for readers interested in the subject, providing an overview which is meticulously researched, authoritative and engaging, and offering broader insights in the areas of journalism, political communication and media studies.